Predicting the efficacy of tofacitinib therapy based on gene expression of proinflammatory cytokines and proteases in cultured blood cells of patients with rheumatoid arthritis - G. A. Markova; E. V. Chetina; A. M. Satybaldyev (Современная ревматология)
The effectiveness of personalized therapy for rheumatoid arthritis (RA) is associated with the correct choice of the drug and the ability to predict its effect before starting the treatment.Objective: to study in patients with RA the relationship between results of therapy and initial expression of genes responsible for bone and articular cartilage resorption (matrix metalloproteinase 9 – MMP9, – cathepsin K) and inflammation (tumor necrosis factor α – TNFα – and interleukin 1β – IL1β) in mononuclear cells of peripheral blood (PBMC), cultured with tofacitinib (TOFA).Patients and methods. We examined 12 patients with RA who had not previously received TOFA. The average age of the patients was 51 years, the average duration of the disease was 37.6 months. After 3 months of TOFA therapy, 6 patients achieved remission, while the rest had high and moderate disease activity. PBMC were isolated before therapy using a Ficoll density gradient and cultured in the presence of 100 nM TOFA for 48 h. Total RNA obtained from these cells was used to analyze the expression of MMP9, cathepsin K, IL1β, and TNFα genes using a real-time quantitative reverse transcription polymerase chain reaction.Results and discussion. TOFA is able to modify gene expression in cultured PBMC from RA patients compared to control cells. The initial expression of all the studied genes was significantly increased in cultured with TOFA cells of patients with persistent high and moderate disease activity during therapy, while TNFα gene expression was significantly reduced in patients who achieved remission.Conclusion. In patients with RA who have not previously received TOFA, a decrease in TNFα gene expression in blood cells cultured with this drug before the start of therapy may be a prognostic biomarker for achieving remission during TOFA therapy.